Botanica Marina (De Gruyter, 1959)
Botanica Marina publishes high-quality contributions from all of the disciplines of marine botany at all levels of biological organisation from subcellular to ecosystem: chemistry and applications, genomics, physiology and ecology, phylogeny and biogeography. Research involving global or interdisciplinary interest is especially welcome as well as applied science papers dealing with emerging conceptual issues or developing technologies.